Climate Change, Socio-economic and Production Linkages in East Malaysia Aquaculture Sector - Rosita, Hamdan; Fatimah, Kari; Siti Muliana, Samsi (IPCBEE, 2012)
Aquaculture sub-sector is the largest contributor to the development of the fisheries sector in Malaysia. Due to its potential and ability to enhance the national food production and resolve social problems in Malaysia, the government allocated substantial funds and planned many programmes related to aquaculture development. Climate change impact on aquaculture production is however uncontrollable and damaging to the aquaculture growth. This study is carried out with the objective of identifying the relationship between production, socio-economic and climate change risks in the aquaculture sector in Sarawak, East Malaysia. This research was conducted on 249 aquaculture ponds and cages farmers in Sarawak. To determine the relationship between all factors, cross-sectional multiple linear regression was employed by using socioeconomic and climate risks data. Socio-economic factors such as number of family members, variable cost and technology usage was found to significantly influence the aquaculture production. Hence, bivariate analysis was employed to indicate the relationship between volumes of annual aquaculture production with all climate change risks factors. The results revealed that increase of climate change risks events have low and significant relationship with decrease in aquaculture productivity. In addition, the qualitative information from the interviews did verify that decrease of dissolved oxygen in water, flood and drought events were common production risks to aquaculture in Sarawak. This study suggests adaptation and mitigation strategies need to be taken immediately to overcome the problem of climate change risks that may be increasing in the future.